Faktor Determinan yang Mempengaruhi Perilaku Caring Perawat Emergency Di Ruang Instalasi Gawat Darurat - Ayatulloh, Daviq; Laily, Nurul Fahmi Rizka; Alfianti, Khalifatus Zuhriyah; Priyantini, Diah; Masruri, Masruri (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: This study aimed to analyze the factors that most influence the caring behavior of emergency nurses in the Emergency Room (IGD) of RSUD Dr. Soetomo, Surabaya. Methods: Quantitative research using a cross sectional approach. A total of 48 respondents were recruited as research samples from 70 populations. The sampling technique used non-probability sampling with purposive sampling. Independent variables are individual factors of personality, psychological factors of motivation, and organizational factors of workload and rewards. Data analysis using SPSS version 21 with multiple logistic regression test with a = 0,05 and 95% confidence level significant. Results: The results showed that there was an influence of individual factors of personality (p=0.047), psychological factors of motivation (p=0.045), organizational factors of workload (p=0.018), and organizational factors of rewards (0.021). The largest Exp (B) value / OR is the workload organizational factor which is 26.150, which means that the perceived workload has a chance of 26.150 times affecting the caring behavior of emergency nurses. Conclusion: Individual personality factors, motivational psychological factors, workload organizational factors and rewards have a significant influence on the caring behavior of emergency nurses. However, there is one factor that most dominantly affects the caring behavior of emergency nurses is the organizational factor of workload.